2003
DOI: 10.1080/0026897021000046762
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the Judd—Ofelt theory in lanthanide—chelidamic acid complexation

Abstract: The coordination chemistry of trivalent lanthanides with chelidamic acid was studied using fluorescence and absorption spectroscopic methods. The speciation was determined using Eu(II1) fluorescence techniques. The stability constants and the oscillator strengths were determined for the Ho(II1) complexes from absorbance measurements of a Ho(II1) hypersensitive transition. The lanthanide coordination chemistry of chelidamic acid and dipicolinic acid is compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the case of [Tb(CDA) 3 ] 6− , the studies have been conducted at a pH above 12 and showed that the deprotonation of the hydroxyl group of CDA (p K a of 10.8)46,50 played a key role in the outer-sphere interactions responsible for the perturbation of the racemic equilibrium by l -amino acids (see later). It should be mentioned that the work discussed in this article represents the first example of using the racemic solution of the 9-coordinate terbium(III) complex with CDA.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of [Tb(CDA) 3 ] 6− , the studies have been conducted at a pH above 12 and showed that the deprotonation of the hydroxyl group of CDA (p K a of 10.8)46,50 played a key role in the outer-sphere interactions responsible for the perturbation of the racemic equilibrium by l -amino acids (see later). It should be mentioned that the work discussed in this article represents the first example of using the racemic solution of the 9-coordinate terbium(III) complex with CDA.…”
Section: Resultsmentioning
confidence: 99%
“…The surprising cocrystallization of the two successive complexes ML + and ML 2 − in compound 2 merits some further comments. According to a recent spectroscopic study, in the Eu 3+ /chelidamic acid system, the most abundant species (of comparable concentration) at low pH, are the successive complexes ML + and ML 2 − . This is in line with the species observed in our solid-state structures, although complexes of the type LnL 3 are generally assumed to be present in solutions at nearly neutral pH .…”
mentioning
confidence: 99%